Whether you like it or not, brand matters - Zazli, Nurul Zakiah; Mohamad Azmin, Nur Azwani (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
Why are people paying so much for a brand, that sometimes they couldn't afford themselves? A mere example could be aiming for a certain product by end of every month every time salary hits. Are people pleasing themselves or others? A question till date, has no specific answer but from years in the media industry, dealing on a day-to-day basis with fast forward fashion. Carrying a brand does provide social acceptance and lets a person fit in a group that they desire. As we all know, everyone wants to be accepted whether at school, work, or social circles. The greater the brand, the broader social acceptance is.